Evaluation of adjuvant chemotherapy in Feline Injection Site-Associated Sarcoma - Pereira, S. T.; Campos, C. B. [UNESP]; Horta, R. S.; Lavalle, G. E.; Araujo, R. B. (FapUNIFESP (SciELO), 2017)
Feline Injection Site-Associated Sarcoma (FISS) is a neoplasm that implies in reduction of quality of life and overall survival in feline patients. A retrospective study of 13 cases of FISS was conducted to evaluate the efficacy of surgical treatment associated to chemotherapy with doxorubicin or carboplatin. Local recurrence occurred in all patients. Patients treated with surgery and chemotherapy presented a longer overall survival and disease-free interval when compared to those that solely received surgical treatment, although no statistical significance was observed (p= 0.3360 and 0.7506, respectively). Surgery remains as the main option for FISS treatment. Further prospective studies with larger samples are warranted to investigate the benefit of chemotherapy for this neoplasm.
Keywords: Carboplatin; Doxorubicin; FISS; Surgery